A BRIEF REVIEW ON PROCESS ANALYTICAL TECHNOLOGY (PAT) - Mali, Akash S.; Jagtap, Monali; Karekar, P.; MARUSKA, A. (International Journal of Current Pharmaceutical Research, 2016)
Process analytical technology (PAT) has been defined as a mechanism to design, analyze and control pharmaceutical manufacturing processes through measurement of critical process parameters which affect critical quality attributes. PAT checks the quality of raw material attributes both physically and chemically (i.e. at off-line, on-line, in-line). PAT involves a shift from testing the quality of building to the quality of products by testing at several intermediate steps. PAT saves a huge amount of time and money required for sampling and analysis of products. The main goal of PAT is to provide successful tools such as multivariate data analysis and acquisition tools, modern process analyzers or analytical chemistry, endpoint process monitoring, controlling tools and continuous improvement and knowledge improvement tools. In this review attempt has been carried out to explore the concept of PAT, different tools of PAT, goals of PAT, How it Works and Its benefits.